2004
DOI: 10.1111/j.0021-8782.2004.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical and ultrastructural characterization of growing colonies of human embryonic stem cells

Abstract: The morphology of human embryonic stem (ES) cells changes with their colonial growth. For a better understanding of the growth of ES cell colonies in culture, we determined their cytochemical and ultrastructural characteristics focusing on images of living cells under a phase contrast microscope. During the initial growth stages, the colonies exhibited a mosaic appearance with discernible cell-cell borders. PAS staining coupled with amylase digestion demonstrated that the bright granules and dark deposits in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
29
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 21 publications
10
29
1
Order By: Relevance
“…Single or clustered rounded protrusions in the cell membrane, in particular the 14-day-old cultures ( Fig. 7D), showed similarity to the coarse particles and halos previously identified by phase contrast microscopy consisting of apoptotic cells and bodies (Johkura et al, 2004). This suggests a pronounced cell death at this late stage.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Single or clustered rounded protrusions in the cell membrane, in particular the 14-day-old cultures ( Fig. 7D), showed similarity to the coarse particles and halos previously identified by phase contrast microscopy consisting of apoptotic cells and bodies (Johkura et al, 2004). This suggests a pronounced cell death at this late stage.…”
Section: Discussionsupporting
confidence: 77%
“…However, according to our TEM investigations, these peripheral monolayers of the intermediate stage colonies grown on MEF exhibited junctional complexes, hence suggesting an epithelial nature. Colonies organized with confined undifferentiated cells and peripheral differentiation was confirmed by a shift in immunoreactivity from the pluripotency marker SSEA-4 to a marker of differentiation SSEA-1 towards the periphery (Johkura et al, 2004). This downregulation in pluripotency markers was to some extent also indicated in the short-term feeder free cultures referred to above, where the intensity in immunostainings of the key pluripotency markers OCT4 and NANOG decreased in peripheral regions (Ullmann et al, 2007).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…When U251 and SHG44 cells were anchored to plates, the different concentrations (0, 120, and 240 mg/L) of nano-HAPs were added, and the U251 and SHG44 cells were incubated for 48 hours; the specimens were postfixed in 1% osmium tetroxide/0.1 M sodium cacodylate buffer, dehydrated in a graded series of ethanol, and embedded after rinsing three times. 10 The ultrathin sections of the specimens were stained with lead citrate and uranyl acetate, and observed with a transmission electron microscope. Each assay was performed in triplicate.…”
Section: Transmission Electron-microscopic Assaymentioning
confidence: 99%
“…Previously, basic fibroblast growth factor and activin A were identified as self-renewal factors (3)(4)(5)(6). However, for reasons that are not clear, hESCs often display high rates of spontaneous apoptosis and differentiation in culture, thus making the process of expanding these cells highly inefficient (3,(7)(8)(9)(10). For example, Dravid et al (8) reported that, under routine culture conditions, Ͼ30% of hESCs undergo spontaneous apoptosis.…”
mentioning
confidence: 99%